Burden of foodborne disease in low-income and middle-income countries and opportunities for scaling food safety interventions - Grace, Delia (Springer, 2023)
Foodborne diseases (FBD) are an important externality of agriculture and food systems, but only since 2015 have they risen up the development agenda. In the first part of this Review, I discuss the multiple burdens of FBD and how they relate to food systems with a focus on low-income and middle-income countries (LMIC), particularly African nations. The health burden of FBD is comparable with that of malaria, and over 90% falls on people in LMIC, with an economic burden of more than US$100 million per year. FBD have many other, less well-estimated effects on nutrition, gender, equity, and the environment. FBD are becoming increasingly prevalent in LMIC and many outbreaks are attributable to nutritious, fresh foods purchased from informal markets. In the second part of the paper, I consider options for improved management of FBD at scale in LMIC. I summarize previous investments in Africa, finding that they have often been poorly directed and evaluated. Finally, on the basis of a systematic literature review, I make recommendations for an integrated framework to evaluate food safety interventions in LMIC, including a typology for interventions and five factors critical for success. Incorporating these factors into food safety interventions will ensure that they are scalable and sustainable.